Stability and control of power systems with high penetrations of inverter-based resources: An accessible review of current knowledge and open questions. (1st November 2020) - Kenyon, Rick Wallace; Bossart, Matthew; Marković, Marija; Doubleday, Kate; Matsuda-Dunn, Reiko; Mitova, Stefania; Julien, Simon A.; Hale, Elaine T.; Hodge, Bri-Mathias
Highlights: Solar photovoltaics use inverters to interface with the AC power system. Inverters do not possess the rotational characteristics of synchronous generators. High instantaneous inverter penetrations complicate traditional stability approaches. Control techniques seen as the primary barrier to high inverter penetrations. Research indicates no fundamental challenges to high inverter penetrations. Abstract: As power system renewable energy penetrations increase, the ways in which key renewable technologies such as wind and solar photovoltaics (PV) differ from thermal generators become more apparent. Many studies have examined the variability and uncertainty of such generators and described how generation and load can be balanced for a wide variety of annual energy penetrations, at timescales from seconds to years. Another important characteristic of these resources is asynchronicity, the result of using inverters to interface the prime energy source with the power system as opposed to synchronous generators. Unlike synchronous generators, whose frequency of alternating current (AC) injection is physically coupled to the rotation of the machine itself, inverter based asynchronous generators do not share the same physical coupling with the generated frequency. These subtle differences impact the operations of power systems developed around the characteristics of synchronous generators. In this paper we review current knowledge and open research questions concerning the interplay between asynchronous inverter-based resources (IBRs) and cycle- to second-scale power system dynamics, with a focus on how stability and control may be impacted or need to be achieved differently when there are high instantaneous penetrations of IBRs across an interconnection. This work does not seek to provide a comprehensive review of the latest developments, but is instead intended to be accessible to any reader with an engineering background and an interest in power systems and renewable energy. As such, the paper includes basic material on power electronics, control schemes for IBRs, and power system stability; and uses this background material to describe potential impacts of IBRs on power system stability, operational challenges associated with large amounts of distributed IBR generation, and modern power system simulation trends driven by IBR characteristics.